1978
DOI: 10.1021/bi00595a016
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone-mediated inhibition of casein mRNA and polysomal casein synthesis in the rat mammary gland during pregnancy

Abstract: The levels of casein mRNA, polysomal casein synthesis, and intracellular casein have been determined during mid-pregnancy in the rat mammary gland. Ovariectomy of the mid-pregnant rat and hormone replacement were used as a model for studying the regulation of casein synthesis. Following ovariectomy a twofold increase in both casein mRNA activity, determined in a wheat germ translation assay, and casein mRNA sequence concentration, measured using a selective cDNA hybridization probe, was observed. This effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

1980
1980
2009
2009

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(29 citation statements)
references
References 45 publications
0
29
0
Order By: Relevance
“…The pregnancy mammary parenchyma, rich in glucocorticoid receptor (26), is exposed to an increased level of circulating glucocorticoid in the pregnant animal (27). The glands also contain abundant casein and its mRNA (28,29). Consequently, preincubation in a medium with insulin and cortisol is required to reduce the endogenous mRNA.. in the explants (12,13).…”
Section: Resultsmentioning
confidence: 99%
“…The pregnancy mammary parenchyma, rich in glucocorticoid receptor (26), is exposed to an increased level of circulating glucocorticoid in the pregnant animal (27). The glands also contain abundant casein and its mRNA (28,29). Consequently, preincubation in a medium with insulin and cortisol is required to reduce the endogenous mRNA.. in the explants (12,13).…”
Section: Resultsmentioning
confidence: 99%
“…1C). The maximal dissociation of YY-1 in cells treated with both hormones was observed by [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] (2). The association of p-pol II at both regulatory regions suggested either the possibility of a long range interaction between the ␤-casein promoter and enhancer or, alternatively, independent recruitment of RNA pol II and perhaps even the transcription of short RNAs at the distal enhancer.…”
Section: Reciprocal Interactions Of Hdac3 and Yy-1 As Compared With Smentioning
confidence: 99%
“…It had been shown that glucocorticoids, prolactin and 17b-estradiol were responsible for the induction of casein gene expression (Groenen and Poel 1994). Glucocorticoids were involved in the induction of casein gene expression (Hobbs et al 1982) while progesterone inhibited casein synthesis during pregnancy (Rosen et al 1978). The expression of milk protein genes is mediated through activation of hormone-responsive elements (HRE) in the promoter region of a gene.…”
Section: Introductionmentioning
confidence: 99%